1993
DOI: 10.1002/cne.903350209
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of the mRNA for a metabotropic glutamate receptor (mGluR3) in the rat brain: An in situ hybridization study

Abstract: Distribution of the mRNA for a metabotropic glutamate receptor, mGluR3, which is coupled to the inhibitory cAMP cascade, was examined in the central nervous system of the adult albino rat by in situ hybridization. The hybridization signals of mGluR3 were detected not only on neuronal cells but also on many glial cells throughout the brain and spinal cord. In the neuronal cells, prominent expression of mGluR3 mRNA was seen in the thalamic reticular nucleus. Moderately labeled neurons were seen in the anterior o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
200
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 474 publications
(219 citation statements)
references
References 77 publications
16
200
1
Order By: Relevance
“…Moreover, in the presence of the selective and potent group 2 metabotropic receptor antagonist LY-341495, NAAG still reduced the NMDAR current following stimulation of the Schaffer collaterals. Indeed, group 2 metabotropic glutamate receptors are unlikely to be involved in the modulation of the CA3 to CA1 synapse examined in this study since mGluR3 receptor activation does not affect Schaffer collateral-evoked EPSCs recorded from CA1 pyramidal cells nor is there appreciable expression of mGluR3 RNA in either CA1 or CA3 pyramidal cells (Ohishi et al, 1993;Gereau and Conn, 1995). Our results with the paired-pulse stimulation are also consistent with a postsynaptic action of NAAG.…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, in the presence of the selective and potent group 2 metabotropic receptor antagonist LY-341495, NAAG still reduced the NMDAR current following stimulation of the Schaffer collaterals. Indeed, group 2 metabotropic glutamate receptors are unlikely to be involved in the modulation of the CA3 to CA1 synapse examined in this study since mGluR3 receptor activation does not affect Schaffer collateral-evoked EPSCs recorded from CA1 pyramidal cells nor is there appreciable expression of mGluR3 RNA in either CA1 or CA3 pyramidal cells (Ohishi et al, 1993;Gereau and Conn, 1995). Our results with the paired-pulse stimulation are also consistent with a postsynaptic action of NAAG.…”
Section: Discussionsupporting
confidence: 80%
“…Approximately 32% of unmyelinated and 28% of myelinated axons in rat digital nerves are positively labeled with antibodies directed against mGluR2/3. Since mRNA for mGluR3 has not been observed in DRG (Ohishi et al, 1993), it is highly likely that the effects reported here represent activation of mGluR2 exclusively. It is most likely that the inhibitory effect of APDC was due to activation of Group II mGluRs constitutively expressed on nociceptors.…”
Section: Localization Of Group II Mglurs On Peripheral Primary Afferentsmentioning
confidence: 89%
“…mGluR 3 is expressed on both pre-and postsynaptic sites in the NAc and the caudate-putamen (Ohishi et al, 1993b;Tamaru et al, 2001). mGluR 2 in these brain areas is selectively expressed on presynaptic sites (Testa et al, 1998;Richards et al, 2005).…”
Section: Neuronal Mechanisms Underlying the Effect Of Ly379268 Nac Inmentioning
confidence: 99%